-11x+9=185

Simple and best practice solution for -11x+9=185 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11x+9=185 equation:


Simplifying
-11x + 9 = 185

Reorder the terms:
9 + -11x = 185

Solving
9 + -11x = 185

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + -11x = 185 + -9

Combine like terms: 9 + -9 = 0
0 + -11x = 185 + -9
-11x = 185 + -9

Combine like terms: 185 + -9 = 176
-11x = 176

Divide each side by '-11'.
x = -16

Simplifying
x = -16

See similar equations:

| x+2(2)=0 | | 6d+5=-4-3d | | X+(x-355)+(2x+80)=2425 | | 3(-2y)+y=-10 | | 18-x=1 | | y=-16-16 | | -2(3y+4)=20 | | -1/3+1= | | 8y-2y+13=2y+12 | | 5w^2-6w+17=8 | | 6x^3-77x^2+56x+8=0 | | 48y-4(6-y)=12(3y+2) | | -3x-14=1 | | fu=3 | | -7(x+8)=35 | | 175x^2-28=0 | | 3a+9b-12= | | 4x+19=7-2x | | -5+4a+3a+6=0 | | 2x-8y=-34 | | -3(x-4)+10=-2 | | -49+9=-5 | | (7x+2)(3x-y)= | | 6(x+4)=3(4-2) | | x(7)=49 | | 2x^2=5-5x | | 3(2x-1)+9=2(3x+3) | | y=28(3)+10 | | 3.2-1.8x=-1.3 | | X^2+10=-25 | | -2x-7(-8x-16)=4 | | y=28x+10 |

Equations solver categories